Purtscher's retinopathy and fat embolism. Issue 8 (August 1989) - Roden, D; Fitzpatrick, G; O'Donoghue, H; Phelan, D
Abstract : A 19-year-old woman who sustained multiple trauma but no head injury developed fulminant fat embolism syndrome (FES). Her neurological deterioration was associated with cerebral oedema and the concomitant Purtscher's type retinopathy. We suggest that the pathogenesis of the retinopathy and of the cerebral oedema are the same and that Purtscher's retinopathy and retinopathy of the FES are indistinguishable.